Entrepreneurship and Transport Policy in Bulgaria - Kirova, Antoaneta (Research Papers, 2005)
The offered for publishing study is aiming at the presentation of the current state and development opportunities of transport entrepreneurship in Bulgaria. Certain fields of transport are covered, such as rail, maritime, river and air sectors, due to the strategic role of those fields as well as the author’s conviction that road transport and infrastructure have already been explored in a lot of studies, papers and dissertations. The forwarding sector has also been removed from the research due to the physical limits in the contents and the fact that this filed is not directly tackled by the transport policy in Bulgaria.The research object can be defined as the opportunities for managing the transport entrepreneurship through the transport policy and for that reason the alterations for securing competitiveness and entrepreneurship in the field of maritime, river, rail and air transport are studied. At the same time, there are some influences on the side of the transport infrastructure shown in the research results.One of the main results is that though with certain difficulties, the sector policy is dedicated to the development necessities due to the future joining to the EU and thus adapting to the entrepreneurial approach, leaving the transport operations to the free market by means of relevant liberalization measures. The governing body – Ministry of transport and communications – is taking an active role in the process of improving the legal background according to the European requirements and the contemporary development of the transport system.The beginning of corporate entrepreneurship in the field of transport, supported by the Ministry of transport and communications and the Regulator National Railway Administration are presented through two comparatively new existing companies – Bulgarian State Railways, PLC and Railway Infrastructure Company.Certain difficulties exist about the policy measures in maritime and river transport, aiming at raising the entrepreneurial activity of carriers and port operators, including private ones. Privatization of the fleet should be carried out as well as concessions of different port occupations. The present financial measures are concerning the Programme for restructuring and modernization of the ports.On the other hand, the realization of the airport modernization programme would bring to the increased traffic to and from Bulgaria as well as the air space. A proposal for a new evaluation of the opportunities for increasing the balance of payments over the use of the transport infrastructure is made.